Menthol: A fresh ergogenic aid for athletic performance - Stevens, C. J.; Best, R. (Sports Medicine, 2017)
The application of menthol has recently been researched as a performance-enhancing aid for various aspects of athletic performance including endurance, speed, strength and joint range of motion. A range of application methods has been used including a mouth rinse, ingestion of a beverage containing menthol or external application to the skin or clothing via a gel or spray. The majority of research has focussed on the use of menthol to impart a cooling sensation on athletes performing endurance exercise in the heat. In this situation, menthol appears to have the greatest beneficial effect on performance when applied internally. In contrast, the majority of investigations into the external application of menthol demonstrated no performance benefit. While studies are limited in number, menthol has not yet proven to be beneficial for speed or strength, and only effective at increasing joint range of motion following exercise that induced delayed-onset muscle soreness. Internal application of menthol may provoke such performance-enhancing effects via mechanisms related to its thermal, ventilatory, analgesic and arousing properties. Future research should focus on well-trained subjects and investigate the addition of menthol to nutritional sports products.